Investor Protection, Ownership, and the Cost of Capital - Himmelberg, Charles P.; Hubbard, R. Glenn; Love, Inessa (World Bank, Washington, D.C., 2013)
The authors combine the agency theory of the firm with risk diversification incentives for insiders. Principal-agent problems between insiders and outsiders force insiders to retain a larger share in their firm than they would under a perfect risk diversification strategy. The authors predict that this higher share of insider ownership and the resulting exposure of insiders to higher idiosyncratic risk will result in underinvestment and higher cost of capital. Using firm-level data from 38 countries, the authors provide evidence in support of their theoretical model, showing that the premium for bearing idiosyncratic risk varies between zero and six percent and decreases in the level of outside investor protection. The results of the study imply that policies aimed at strengthening investor protection laws and their enforcement will improve capital allocation and result in higher growth.